Finite 2-groups with some prescribed minimal nonabelian subgroups - Janko, Zvonimir (Journal of algebra and its applications, 2017)
We determine up to isomorphism finite nonabelian 2-groups all of whose minimal nonabelian subgroups, except one, are isomorphic to D8 (Theorem 1) and also, we determine finite nonabelian 2-groups all of whose minimal nonabelian subgroups, except one, are isomorphic to Q8 (Theorem 2).
Published online: 26 August 2016
Gesehen am 22.02.2018